Colonization with Ceftriaxone-resistant Enterobacteriaceae and Risk of Bacteremia in Patients Receiving Induction Chemotherapy for Acute Leukemia. (4th October 2017) - Satlin, Michael; Chavda, Kalyan D; Hovan, Michael; Chen, Liang; Westblade, Lars; Chavda, Bhakti; Helfgott, David; Roboz, Gail; Jenkins, Stephen G; Kreiswirth, Barry N; Walsh, Thomas J
Abstract: Background: Bacteremia caused by ceftriaxone-resistant Enterobacteriaceae (CRO-R-E) is associated with inadequate empirical therapy and high mortality in neutropenic patients. Increased knowledge of rates of CRO-R-E colonization and risk of bacteremia in these patients is needed. Methods: From November 2015 to Apr 2017, we collected stool or perianal swab samples from patients with acute leukemia upon initiation of induction chemotherapy and weekly thereafter during neutropenia. Patients with less than 7 days of neutropenia while an inpatient were excluded. We plated samples onto ESBL screening agar, identified isolated bacteria, performed antimicrobial susceptibility testing, and screened CRO-R-E for β-lactamase genes by PCR. We then determined the prevalence of CRO-R-E colonization at the onset of chemotherapy and the incidence of acquiring CRO-R-E or developing CRO-R-E bacteremia during the hospitalization. Results: We analyzed 82 patients. Their median age was 65 years, 76% had acute myeloid leukemia, and the median duration of neutropenia was 19 days. Nineteen patients (23%) were initially colonized with CRO-R-E, including 13 (20%) of 66 patients with newly diagnosed leukemia and 6 (38%) of 16 patients with relapsed or refractory disease. Only one of the colonized patients received prophylactic levofloxacin. There were 23 colonizing CRO-R-E, of which Escherichia coli ( n = 13), Klebsiella pneumoniae ( n = 4) and Citrobacter spp. ( n = 4) were most common. Antimicrobial susceptibility rates were ceftazidime (13%), cefepime (26%), piperacillin-tazobactam (70%), and meropenem (91%). Thirteen (56%) were ESBL-producers, 8 (35%) produced AmpC β-lactamases, and 2 (9%) produced K. pneumoniae carbapenemase (KPC). Of patients not initially colonized with CRO-R-E, 5% acquired CRO-R-E. Two (11%) of the 19 patients colonized with CRO-R-E developed CRO-R-E bacteremia (one CTX-M-producing E. coli and one KPC-producing K. pneumoniae ), whereas 6 (32%) developed bacteremia due to CRO-susceptible Enterobacteriaceae. By comparison, only 1 (2%) of 63 patients not initially colonized with CRO-R-E developed CRO-R-E bacteremia ( P = 0.13). Conclusion: Patients with acute leukemia had high rates of colonization with CRO-R-E. However, the risk of CRO-R-E bacteremia in colonized patients was modest in the absence of levofloxacin prophylaxis. Disclosures: M. Satlin, Hardy Diagnostics: Investigator, Research support. Allergan: Grant Investigator, Research grant. Merck: Grant Investigator, Grant recipient. S. G. Jenkins, Cormedix: Consultant, Consulting fee. Bayer: Consultant, Consulting fee. Merck: Grant Investigator and Scientific Advisor, Research grant. T. J. Walsh, The Medicines Company: Consultant and Investigator, Consulting fee and Research grant. Astellas: Consultant and Investigator, Consulting fee and Research grant. Allergan: Consultant and Investigator, Consulting fee and Research grant. Merck: Consultant and Investigator, Consulting fee and Research grant